HAK DAN KEWAJIBAN ISTRI : PERAN ISTRI DALAM RANAH DOMESTIK DAN KARIER (Studi Kasus di Desa Margahayu Kecamatan Manonjaya Kabupaten Tasikmalaya) - Gunadi; Nida Amalia Dewi (Ahwaluna | Jurnal Hukum Keluarga Islam, 2023)
In this modern era, many wives not only play a role in the household as mothers (domestic role), but also in society with various functions and positions (public role/career). As was found in Margahayu Village, Manonjaya District, Tasikmalaya Regency, there are quite a number of wives who not only play a role in the domestic sphere, taking care of the household and family, but they also play a role in the public sphere. The purpose of this research is to find out the rights and obligations of wives in the domestic sphere, to know the rights and obligations of wives in the career realm, to find out the strategies of wives who work as career women in balancing the role of mother, between career and family. The method that the author uses is a qualitative research method, namely research procedures that produce descriptive data in the form of written or spoken words or people or actors observed in the field (field research), namely research whose object is about symptoms or events that occur in community groups. So this research can also be called case research or case study with a qualitative descriptive approach. In Margahayu Village, Manonjaya District, Manonjaya District, Tasikmalaya Regency, it was found through interviews that several wives who became career women stated that nothing prevented them from having a career, even though they were already married, had husbands and children. They don't mind the cultural norms that say that after marriage and becoming a wife, women have to take on more household responsibilities. Strategies in balancing the mother's role, between career and family, namely with quality time, good communication, openness, mutual understanding, managing time as best as possible, husband's support, maintaining family integrity by trying to understand each other